Determining the endurance limit of AISI 4340 steels in terms of different statistical approaches (Fracture and Structural Integrity, 2021)
In engineering applications, fatigue phenomenon is a key issue and needs to be analyzed in the beginning of design phase in case of any component exposed to alternating loading on operation otherwise catastrophic fatigue failure may cause. Component can be designed with safe-life, fail-safe, and damage tolerant approach based on whether redundant load path and damage sensitive. Before starting analyzing the structure, material allowable data needs to be presented in a reliable way to predict fatigue life of components. SN curves with presented confidence levels are the robust approach to make a prediction on safe life of a structure in terms of fatigue. In this point, there are so many approaches to determine fatigue limit of materials and issue shall be handled by statistical manner. In literature, different staircase and curve fitting methods were presented to estimate endurance limit of materials and some reliability manuscript published. In this paper, fatigue limit of AISI 4340 steel will be investigated through most convinced staircase and curve fitting approaches and their reliability will be queried.
Keywords: Steels; Fatigue; Staircase; Curve Fitting; Reliability